2020
DOI: 10.14334/jitv.v25i2.2498
|View full text |Cite
|
Sign up to set email alerts
|

Non-Genetic and Genetic Effects on Growth Traits from Birth to 120 days of Age of G2 Sapera Goat

Abstract: Information on non-genetic and genetic factors is required in the selection program. Indonesian Research Institute for Animal Production (IRIAP) has been conducting a selection of the growth traits of Sapera goat (50% Saanen, 50% PE).  This research was aimed to study non-genetic and genetic effects on growth traits from birth to the age of 120 days old of the 2<sup>nd </sup>generation (G<sub>2</sub>) of Sapera goat.  Data on body weight and measurement were collected from kids at birth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
3
0
2
Order By: Relevance
“…Saanen from Italy, La Mancha, Saanen from Croatia, Camosciata delle Alpi, Charmoisée, Murciano-Granadina, and Alpine are dairy goat breeds that have high milk production. In Indonesia, crosses of Saanen and Etawah Grade (Sapera) are carried out to obtain a breed with high milk production with tropical climate resistance [12]. In Brazil, Saanen and Anglo-Nubian breeds were crossed in an effort to strengthen the rusticity [13].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Saanen from Italy, La Mancha, Saanen from Croatia, Camosciata delle Alpi, Charmoisée, Murciano-Granadina, and Alpine are dairy goat breeds that have high milk production. In Indonesia, crosses of Saanen and Etawah Grade (Sapera) are carried out to obtain a breed with high milk production with tropical climate resistance [12]. In Brazil, Saanen and Anglo-Nubian breeds were crossed in an effort to strengthen the rusticity [13].…”
Section: Resultsmentioning
confidence: 99%
“…In Brazil, Saanen and Anglo-Nubian breeds were crossed in an effort to strengthen the rusticity [13]. Sapera has a higher production than Etawah Grade [10,11] and has a higher fat content than Saanen [6,10,12]. Sapera, Sarda Primitiva, and Etawah Grade have a higher fat content among other breeds.…”
Section: Resultsmentioning
confidence: 99%
“…Based on previous studies have reported that genetic polymorphisms of the SCD gene were associated with fatty acid quality, provided in dairy cattle (Alim et al, 2012;Asmarasari et al, 2020), goats (Avilés et al, 2016), pigs (Fernández-Barroso et al, 2020), and chicken (Furqon et al, 2017). Differences in fatty acid composition can be caused by differences in feed consumption (Alsharari et al, 2020), breed, and genetic factors (Anggraeni et al, 2020). The SCD enzyme activity was significantly related to unsaturated fatty acids (UFA), especially in bovine fat tissue (Li et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Produksi air susu induk nyata (P<0,05) dipengaruhi oleh litter size, dalam hal ini, dengan pemberian pakan yang lebih baik ternyata produksi susu Kambing PE beranak kembar 14% lebih tinggi dibanding produksi susu induk beranak tunggal (803 vs 989 ml). Hasil ini sesuai dengan Butterworth et al (1998) dan Anggraeni et al (2020), bahwa litter size adalah salah satu factor yang mempengaruhi produksi susu kambing pedaging. Demikian pula pendapat Owen (1989), Peart et al (1992) dan Sitorus et al (2005), bahwa produksi susu induk beranak kembar lebih tinggi dibanding induk beranak tunggal.…”
Section: Hasil Dan Pembahasanunclassified
“…Hal ini, menurut Silitonga dan Kuswandi ( 2004), karena frekuensi menyusu anak kembar secara keseluruhan lebih banyak disbanding anak tunggal sehingga menimbulkan refleksi neuroendokrin lebih sering. Akibat reflek ini adalah dilepaskannya hormone oxytoxin yang lebih banyak ke peredaran darah yang beraksi pada sel myoepithel (sel otot halus) sekitar alveoli kelenjar ambing sehingga air susu siap dikeluarkan dari kelenjarnya (Hafez, 1987;Anggraeni et al, 2020).…”
Section: Hasil Dan Pembahasanunclassified